Mosque Management in Urban City: Bargaining between the Sacred and the Social Challenges - Safei, Agus Ahmad; Armstrong, Paul Salahuddin (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
A mosque serves as a pivotal element in the structure of a Muslim community.Â The function of a mosque extends beyond its religious capacity as a place for worship, playing a vital role in addressing the social problems that the community faces. To explore this, the present study focuses on the strategy employed by Masjid Raya Bandung to manage and overcome various social problems around its vicinity. Utilising a descriptive-analytical approach, the present study aims to depict the existing social phenomena around Masjid Raya Bandung (The Grand Mosque of Bandung) in the Province of West Java, Indonesia, with specific research variables.Â Non-documentary data is obtained through participant observation and in-depth interviews. Located in the city's heart, across the city hall, a place of public gathering, the Grand Mosque of Bandung operates within a business and materialistic environment. The faced challenges include sanitation issues, unregulated street vendors tied to an informal economy, prevalent crime, covert prostitution in the vicinity, and escalating consumerism from nearby shopping centres. The study underscores the mosque as not only a spiritual oasis but also a socio-religious institution actively participating in providing solutions for various social issues within its urban setting. It is confirmed that the mosque's function is not only for ritual things but also for social activities in urban Islamic societies, particularly in managing and overcoming various social problems that surround the mosque.Â